Mechanisms of action and effects of the administration of Coenzyme Q10 on metabolic syndrome - Daniela Casagrande; Paulo H. Waib; Alceu Afonso Jordão Júnior (Journal of Nutrition & Intermediary Metabolism, 2018)
Coenzyme Q10 (CoQ10) is an essential component of the mitochondrial electron transport chain responsible for different functions, among them its action as an antioxidant compound. Low CoQ10 levels are related to inflammatory processes and oxidative stress, factors implicated in atherosclerosis, obesity, nonalcoholic fatty liver (NAFLD), as well as metabolic syndrome (MS). MS is a disease characterized by cardiovascular risk factors linked to obesity, dyslipidemia and hyperglycemia. NAFLD is recognized as a hepatic manifestation of MS and, together with the latter, has a high incidence in the world population. Recent investigations have underscored the positive effects of CoQ10 supplementation on the treatment of obesity, oxidative stress, MS, and NAFLD. The objective of the present study was to analyze the evidence of the effects of CoQ10 supplementation on MS and NAFLD and to provide a general view of the mechanisms of action of CoQ10 in both diseases. Keywords: Metabolic syndrome, Coenzyme Q10, Nonalcoholic fatty liver disease, Oxidative stress, Inflammation